The role of mixed orchards in carbon sequestration and climate change mitigation in a Mediterranean island environment - Sotiroula Ioannidou; Sotiroula Ioannidou; Vassilis D. Litskas; Menelaos Stavrinides; Ioannis N. Vogiatzakis; Ioannis N. Vogiatzakis (Frontiers in Sustainable Food Systems)
Mixed orchards, planted with different species of tree crops, are a form of a traditional cropping system that has been practiced for millennia in the Mediterranean and provides the important ecosystem service of carbon sequestration. We used six allometric equations (M1-M6) based on existing literature and data from 49 orchards for estimating tree total biomass (TB) and carbon sequestration, based on C content of dry biomass. A species/geographically-specific equation (M1), a genus-specific (M2), a genus/geographically-specific forest equation (M3), two generalized forest allometric equations (M4 and M5) and a generalized agricultural landscape equation (M6) were compared and yielded an average of 15.42, 10.80, 11.39, 6.12, 6.66, and 9.88 Mg C ha−1, respectively. Organic and conventional orchards at the same productive stage did not differ significantly from each other in CO2 sequestration (CO2seq) per tree per year (10.42 and 10 kg CO2eq, respectively). Equation M1, was considered as the most representative (species and environment) for use in perennial Mediterranean orchards. The use of allometric equations is proposed as a simple, effective, and efficient method to estimate CO2 sequestration from mixed orchards using easily measurable biometric characteristics of the trees. The findings are important for the future estimation of CO2 stocks of agricultural landscapes.